Application of agro-waste adsorbent for the removal of cod in wastewater - Nasir, Nazlizan; Daud, Zawawi; Abdul Kadir, Aeslina (Penerbit UTHM, 2021)
Adsorbent from abundant residues of palm oil known as empty fruit bunch (EFB) was prepared to investigate the removal of Chemical Oxygen Demand (COD) from natural rubber wastewater. The EFB was modified using citric acid (CA) to enhance adsorption ability. The adsorption conditions such as adsorbent dose, pH and contact time for the effective removal of COD were optimized. Isotherms were generated to describe the removal of the COD. Results have shown that the optimum reaction conditions for COD adsorption by the EFB were 3 g of adsorbent, pH 7 and 120 min as contact time for the effective removal 76% of COD in natural rubber wastewater. Meanwhile, the adsorption data for COD on the EFB fitted the Langmuir isotherm, suggesting a monolayer adsorption behaviour of the adsorption processes. This study indicated EFB is a promising candidate adsorbent for the removal of COD in wastewater.